Kombinasi Insulin Basal Dengan GLP-1 RA Dalam FRC (IGLARLIXI) Terhadap Pencapaian Target DM Tipe 2 - Maria Cecilia Gritce Widjaja (Syntax Corporation Indonesia, 2022)
Management of diabetes melitus in Indonesia still needs to be improved, the presence of inertia at the time of initiation and intensification of insulin makes the HbA1c target not achieved (<7%). The use of basal insulin often does’nt give satisfactory results, seen from providing HbA1c, the risk of hypoglycemia, and weight gain. The purpose of this literature is to discuss the combination of basal insulin with GLP-1RA (iGlarLixi). Methods The writing of this literature uses a narrative review. Based on a review that has been reviewed, the use of iGlarLixi is superior to insulin alone in the treatment of DM. iGlarLixi provides HbA1c targets <7% more achieved, the risk of hypoglycemia that often occurs with basal insulin use, weight gain also didn’t occur and conversely iGlarLixi can provide a weight loss effect. iGlarLixi can be the first choice in patients with type 2 diabetes who are not controlled with insulin